Carfilzomib: A cause of drug associated thrombotic microangiopathy. Issue 3 (June 2016) - Qaqish, Ibrahim; Schlam, Ilana M.; Chakkera, Harini A.; Fonseca, Rafael; Adamski, Jill
Abstract: Carfilzomib is a selective proteosome inhibitor approved for treatment of relapsed and refractory multiple myeloma. Recent reports have linked exposure to carfilzomib with development of thrombotic microangiopathy (TMA). We describe two cases of biopsy proven thrombotic microangiopathy that occurred after the initiation of carfilzomib (dosed at 32 mg/m 2 and 23 mg/m 2, respectively) for relapsed multiple myeloma. Both patients were managed with discontinuation of the drug, therapeutic plasma exchange (TPE) and supportive care. Hemoglobin, platelets and renal function did not improve with TPE. TMA resolved with creatinine returning to baseline several weeks after discontinuation of the drug. The outcomes suggest that TPE is not beneficial for treating carfilzomib-induced TMA.